Localización de las neoplasias epiteliales de intestino grueso en el perro: estudio retrospectivo de 24 casos clínicos - Rodríguez-franco, F.; Sainz, A.; Carrasco, V.; Benítez, S.; García-sancho , M.; Mancho, C.; Benito , A.; Rodríguez-bertos , A. (Revista Complutense de Ciencias Veterinarias, 2008)
The aim of this paper was to study the localization of epithelial neoplasia affecting the large intestine in dogs. A retrospective study was performed on 24 dogs that had large intestine epithelial neoplasia. The rectal segment of the large intestine was the place where the epithelial neoplasia were more commonly found. According to the results of the current study, 75% of the cases were affecting the rectum. All adenomas were located in the rectum, while none of them were in more cranial segments of the large bowel. In contrast, carcinomas were equally distributed between the rectum and the descendent colon.
Keywords: Epithelial neoplasia; Adenoma; Carcinoma; Large intestine; Dog